Hybrid DFT study of MWCNT/Zr-doped SrTiO3 heterostructure: Hydrogen production, electronic properties and charge Carrier mediator role of Zr4+ ion. (6th December 2018) - Opoku, Francis; Govender, Krishna Kuben; Catharina Elizabeth van Sittert, Cornelia Gertina; Govender, Penny Poomani
Abstract: Over the past decade, remarkable efforts have been made to design low-cost, non-toxic, stable and efficient photocatalyst for water splitting. In the present work, an effective alternative approach to enhance hydrogen production of SrTiO3 was by coupling with MWCNT to form heterojunction followed by doping with Zr 4+ ion. The observed type-II band alignment and the polarised electric field could promote the separation of photoexcited charge carriers and photocatalytic activity of these hybrid heterostructures. The theoretical calculation revealed that Zr 4+ ion could act as a charge carrier mediator to transfer electrons to the SrTiO3 surface. The MWCNT (6, 12, 18)/Zr-doped SrTiO3 (100) heterostructure exhibited excellent activity due to the combined effect of MWCNT (6, 12, 18) and Zr-doped SrTiO3 (100) monolayers compared with pure SrTiO3 . This study offers a novel understanding of designing highly active and stable SrTiO3 -based photocatalyst as efficient hydrogen generation material. Highlights: A hybrid MWCNT/Zr–doped SrTiO3 for H2 generation was studied via DFT calculation. The size of MWCNT influenced the amount of interfacial charge transfer. The interfacial interaction between MWCNT and SrTiO3 induced bandgap reduction. Zr ion acted as acceptor and donor to boost the photoactivity.